Fluorescein-Assisted Microsurgical Resection of Vestibular Schwannoma: A Prospective Feasibility Study. Issue 10 (14th December 2022) - Chan, Stephen A.; Macielak, Robert J.; Tuchscherer, Amy M.; Neff, Brian A.; Driscoll, Colin L.W.; Peris-Celda, Maria; Van Gompel, Jamie J.; Link, Michael J.; Carlson, Matthew L.
Abstract : Objective: To evaluate the optimal dose and timing of administration of sodium fluorescein (SF) for selective fluorescence of sporadic vestibular schwannoma (VS) during microsurgery with the YELLOW 560-nm microscope filter (YE560) and to characterize the potential benefit of this fluorescence as determined by intraoperative surgeon assessment. Study Design: Prospective cohort study. Setting: Tertiary referral center. Patients: Adult patients undergoing VS microsurgery. Interventions: Intraoperative intravenous administration of SF and visualization with the YE560. Main Outcome Measures: Time to differential fluorescence, duration of fluorescence, correlation of fluorescence of VS with electrostimulation and white light microscopy visual assessment, and likelihood of surgeons to use SF with the YE560 in future cases. Results: Novel use of SF and YE560 during microsurgery achieved selective fluorescence of VS with capabilities to differentiate nerve fascicles and tumor approximately 30 minutes after administration. Nuances of SF administration and timing are discussed. Seventy-five percent of surgeons observed an excellent correlation of selective fluorescence with white light microscopy. Representative images and cases are presented. Conclusions: SF and YE560 may be used in VS microsurgery to visually differentiate VS from surrounding nerves. Potential benefits include enhanced visualization of the tumor–nerve interface for tumor dissection and detection of any residual disease, such as in the fundus after hearing preservation microsurgery.